1995
DOI: 10.1002/jlb.57.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for LFA-1/ICAM-1 dependent stimulation of protein tyrosine phosphorylation in human B lymphoid cell lines during homotypic adhesion

Abstract: JK32.1 and SKW6.4 are Epstein-Barr virus (EBV)-positive human B cell lines that undergo spontaneous, lymphocyte function-associated antigen 1 (LFA-1) dependent homotypic adhesion in culture. This process is associated with induction of tyrosine phosphoproteins of molecular mass 90, 106, and 120 kDa and could be reproduced when these cells were centrifugationally aggregated. Antibodies to the beta 2 (CD18) chain of LFA-1 interfered with induction of p120, p106, and p90 during cellular aggregation. Response indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Unlike the ␤ 1 family of integrins, LFA-1-mediated adhesion does not activate or stimulate the phosphorylation of the p125 FAK kinase (Fig. 1) or other members of the c-src gene family (38,48). However, here we demonstrate that adhesion mediated through LFA-1⅐ICAM-1 binding leads to tyrosine phosphorylation of p130 cas .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Unlike the ␤ 1 family of integrins, LFA-1-mediated adhesion does not activate or stimulate the phosphorylation of the p125 FAK kinase (Fig. 1) or other members of the c-src gene family (38,48). However, here we demonstrate that adhesion mediated through LFA-1⅐ICAM-1 binding leads to tyrosine phosphorylation of p130 cas .…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, it has been reported that phospholipase C␥ is phosphorylated on tyrosine residues upon cross-linking of LFA-1 by antibody (36). It has also been reported that activation of LFA-1 in B cells (JK32.1) and T-cells (JM) results in enhanced tyrosine phosphorylation of a set of yet unknown proteins (37,38). In this report, we demonstrate that activation of LFA-1, by either stimulation of inside out signaling pathways or through a ␤ 2 subunit-specific activating antibody, results in enhanced tyrosine phosphorylation of p130 cas and subsequent association with crkII.…”
mentioning
confidence: 99%
“…First, cytokines, especially TNF-α, restructure the intercellular junctions, which facilitate leukocyte transmigration (66). Cytokines activate ECs and induce endothelial expression of integrin ligands, especially vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1, which lead to the recruitment of more inflammatory cells into the inflammatory lesions (7, 68, 69). In KD, it has been proposed that inflammatory cells recruited by macrophage cytokines damage the ECs and smooth muscle cells (SMCs), initiating complex inflammatory responses underlying vasculitis (64).…”
Section: Pathogenic Functions Of Macrophages In Vascular Inflammationmentioning
confidence: 99%
“…The intercellular adhesion molecule 1, ICAM-1 (also known as CD54) is expressed by endothelial and immune cells and is involved in several important immunological events, such as activation of CD8 + T cells [29], signaling between lymphoid cells [30], [31], and trans-endothelial migration of leukocytes [32][34]. ICAM-1 is a specific ligand for LFA-1 (lymphocyte function-associated antigen-1), which is an integrin-like protein expressed by immune cells [35][37].…”
Section: Introductionmentioning
confidence: 99%